Cortical Porosity Identifies Women with Osteopenia at Increased Risk for Forearm Fractures - Bala, Yohann (2014)
BACKGROUND: Most fragility fractures arise among the many women with osteopenia, not the smaller number with osteoporosis at high risk for fracture. Thus, most women at risk for fracture assessed only by measuring areal bone mineral density (aBMD) will remain untreated. METHODS: We measured cortical porosity and trabecular bone volume/total volume (BV/TV) of the ultradistal radius (UDR) using high-resolution peripheral quantitative computed tomography, aBMD using densitometry, and 10-year fracture probability using the country-specific FRAX tool in 68 postmenopausal women with forearm fractures and 70 age-matched community controls in Olmsted County, Minnesota. RESULTS: Women with forearm fractures had 0.4 standard deviations (SD) higher cortical porosity and 0.6 SD lower trabecular BV/TV. Compact-appearing cortical porosity predicted fracture independent of aBMD; odds ratio [OR] 1.92 (95%CI, 1.10–3.33). In women with osteoporosis at the UDR, cortical porosity did not distinguish those with, from those without, fractures because high porosity was present in 92% and 86% of each group respectively. By contrast, in women with osteopenia at the UDR, high porosity of the compact-appearing cortex conferred an OR for fracture of 4.00 (95%CI, 1.15–13.90). CONCLUSION: In women with osteoporosis, porosity is captured by aBMD and so measuring UDR cortical porosity does not improve diagnostic sensitivity. However, in women with osteopenia, cortical porosity was associated with forearm fractures.